Survey on the run‐time systems of enterprise application integration platforms focusing on performance. (13th December 2018) - Freire, Daniela L.; Frantz, Rafael Z.; Roos‐Frantz, Fabricia; Sawicki, Sandro
Summary: Companies are taking advantage of cloud computing to upgrade their business processes. Cloud computing requires interaction with many kinds of applications, so it is necessary to improve the performance of software tools that allow keeping information on all these applications consistent and synchronised. Integration platforms are specialised software tools that provide support to design, implement, run, and monitor integration solutions, which aim to orchestrate a set of applications so as to promote compatibility among their data or to develop new functionality on top of the current ones. The run‐time system is the part of the integration platform responsible for running the integration solutions, which makes its performance the uttermost important issue. The contribution of this article is two‐fold: a framework and an evaluation of integration platforms. The former is a framework composed of ten properties grouped into two dimensions to evaluate the run‐time systems focusing on performance. Using this framework as reference, the second contribution is an evaluation of nine open‐source integration platforms, which represent the state‐of‐the‐art, provide support to the integration patterns, and follow the pipes‐and‐filters architectural style. In addition, as a result of this work, we suggest open research directions that can be explored to improve the performance of the run‐time systems and at the same time may be useful to adapt them to the context of cloud computing.